2018
DOI: 10.1111/are.13798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary humic acid on growth performance, haemato-immunological and physiological responses and resistance of Rainbow trout,Oncorhynchus mykisstoYersinia ruckeri

Abstract: This study investigated the effects of dietary humic acid sodium salt on growth performance, haemato-immunological and physiological responses, and resistance of rainbow trout, Oncorhynchus mykiss to Yersinia ruckeri. The experimental fish were divided into four groups; three of them were fed with humic acid incorporated diets (0.3% H3, 0.6% H6, 1.2% H12) and an additive free basal diet served as the control.Growth performance and haematological parameters of rainbow trout were not affected by humic acid suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
32
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 67 publications
13
32
2
2
Order By: Relevance
“…In the current study, among different pancreatic enzymes analysed only specific activity of chymotrypsin improved in fish fed diets administered with NaDF compared to the control group. Other studies reported that pancreatic digestive enzymes increased by administrating dietary OA such as citric acid in hybrid tilapia ( O. niloticus × Oreochromis aureus , Li, Li, & Wu, ), western whiteleg shrimp (Su et al, ) and red drum ( S. ocellatus , Castillo et al, ), and humic acid in rainbow trout (Yilmaz, Ergun, Celik, & Yigit, ). In this regard, da Silva et al () evaluated in vitro pancreatic enzyme activity in western whiteleg shrimp and found that trypsin and chymotrypsin activity increased in the presence of acetate and propionate, but decreased in the presence of lactate and citrate.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, among different pancreatic enzymes analysed only specific activity of chymotrypsin improved in fish fed diets administered with NaDF compared to the control group. Other studies reported that pancreatic digestive enzymes increased by administrating dietary OA such as citric acid in hybrid tilapia ( O. niloticus × Oreochromis aureus , Li, Li, & Wu, ), western whiteleg shrimp (Su et al, ) and red drum ( S. ocellatus , Castillo et al, ), and humic acid in rainbow trout (Yilmaz, Ergun, Celik, & Yigit, ). In this regard, da Silva et al () evaluated in vitro pancreatic enzyme activity in western whiteleg shrimp and found that trypsin and chymotrypsin activity increased in the presence of acetate and propionate, but decreased in the presence of lactate and citrate.…”
Section: Discussionmentioning
confidence: 98%
“…Other tissues were weighed in Eppendorf tubes after by adding cold distilled water ten times their weight on them. Samples were centrifuged, and upper phases of them were stored at −80°C until digestive enzyme analyses (Yılmaz, Ergun, Çelik, & Yigit, ).…”
Section: Methodsmentioning
confidence: 99%
“…The pH values in feed particles, the intestines (from pyloric caeca to anus) and stomach were measured using a pH meter after weighing the samples and diluting for ten times with distilled water as earlier described by Yilmaz, Ergun, Çelik et al (). The concentration of pepsin, amylase, lipase, alkaline phosphatase and trypsin was estimated from the absorbance at 280 nm, 540 nm, 405 nm, 405 nm and 410 nm, respectively, according to the methods previously conducted and described in our laboratory (Yilmaz, Ergün, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the scientific community has begun to search for alternative non‐antibiotic‐related strategies, including phage therapy, immunostimulant therapy, treatment with dietary herbal medications (Mabrok & Wahdan, ; Newaj‐Fyzul & Austin, ; Yilmaz, ; Yılmaz & Ergün, ; Yılmaz, Ergün, & Soytaş, ; Yilmaz, Ergün, & Turk, ), and supplementation with organic acids (Yilmaz, ; Yılmaz & Ergün, ; Yılmaz, Ergun, Çelik, & Yigit, ; Yilmaz, Ergün, & Yıgıt, ), probiotics, prebiotics and synbiotics (Defoirdt, Sorgeloos, & Bossier, ; Di Bartolomeo, Startek, & Van den Ende, ; Gatesoupe, ).…”
Section: Introductionmentioning
confidence: 99%